Semi-analytic forecasts for JWST – VI. Simulated light-cones and galaxy clustering predictions. Issue 4 (31st July 2022) - Yung, L Y Aaron; Somerville, Rachel S; Ferguson, Henry C; Finkelstein, Steven L; Gardner, Jonathan P; Davé, Romeel; Bagley, Micaela B; Popping, Gergö; Behroozi, Peter
ABSTRACT: In anticipation of the new era of high-redshift exploration marked by the commissioning of the James Webb Space Telescope ( JWST ), we present two sets of galaxy catalogues that are designed to aid the planning and interpretation of observing programs. We provide a set of 40 wide-field light-cones with footprints spanning approximately ∼1000 arcmin 2 containing galaxies up to z = 10, and a new set of eight ultradeep light-cones with 132 arcmin 2 footprints, containing galaxies up to z ∼ 12 down to the magnitudes expected to be reached in the deepest JWST surveys. These mock light-cones are extracted from dissipationless N -body simulations and populated with galaxies using the well-established, computationally efficient Santa Cruz semi-analytic model for galaxy formation. We provide a wide range of predicted physical properties, and simulated photometry from Near-Infrared Camera (NIRCam) and many other instruments. We explore the predicted counts and luminosity functions and angular two-point correlation functions for galaxies in these simulated light-cones. We also explore the predicted field-to-field variance using multiple light-cone realizations. We find that these light-cones reproduce the available measurements of observed clustering from 0.2 ≲ z ≲ 7.5 very well. We provide predictions for galaxy clustering at high redshift that may be obtained from future JWST observations. All of the light-cones presented here are made available through a web-based interactive data release portal.